VEGF inhibition as possible therapy in spondyloarthritis patients: Targeting bone remodelling. (April 2017) - Lacout, Alexis; Carlier, Robert Yves; El Hajjam, Mostafa; Marcy, Pierre Yves
Abstract: Spondyloarthritis refers to a group of chronic inflammatory rheumatic diseases that predominantly affects the axial skeleton, causing pain and stiffness. Human bone is highly dynamic organ that interacts with a wide array cells and tissues. Process of bone remodelling relies on a delicate balance between bone formation and bone resorption, orchestrated by osteoblasts and osteoclasts. Disruption of this homeostatic balance of bone removal and replacement can manifest as inappropriate new bone formation found in spondylarthritis. We hypothesize that VEGF may promote bone remodelling, stimulate angiogenesis, and both osteoclastic and osteoblastic activity. Anti VEGF may be tested as a dedicated therapy to prevent bone remodelling in spondyloarthritis patients, namely in cases of aggressive disease. Bone remodelling could be monitored by using [18F]Fluoride PET scan.